The Marrano specter : Derrida and Hispanism - Graff Zivin, Erin (Fordham University Press, 2018)
The Marrano Specter brings together work by major scholars who collectively pursue the reciprocal influence between Jacques Derrida and Hispanism: his reception within intellectual circles in Spain and Latin America, on the one hand, and the Hispanist or marrano inflection of Derrida's philosophical writings on the other.